The Cosmic Horizon as the Highest Heaven: Examining Michael Guillen's Hypothesis - Belay Sitotaw Goshu; Muhammad Ridwan (Budapest International Research and Critics University, 2026)
The human tendency to locate the divine in spatial terms represents a cognitive universal, yet classical theism affirms divine transcendence, the claim that God as Creator cannot be contained within creation. Into this tension steps physicist Michael Guillen, who has proposed that the